World Controversy: Water Sustainability In An Environmental Accounting Perspective - Mediaty, Mediaty; Rante, Matrik Irama; Habbe, Abdul Hamid (Advances In Social Humanities Research, 2024)
Social and environmental concerns have emerged as globally compelling topics, necessitating attention from all stakeholders due to their significant impact on human life. Sustainable global economic development is intricately tied to the Triple Bottom Line concept, emphasizing Profit, People, and Planet. Among critical natural resources, water resources play a central role across various economic sectors, especially amidst escalating global water scarcity and degradation challenges. While research in this area has evolved significantly, many studies remain limited in scope, focusing on specific processes or regions and failing to provide comprehensive insights into water usage across different sectors. Building upon previous research, this study employs a Systematic Literature Review (SLR) method from 2019 to 2023 to understand trends and progress in water sustainability accounting research. Through the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method, 23 relevant articles were identified and analyzed from various publishers such as Elsevier, Emerald, MDPI, and others. The findings reveal a diverse distribution of articles across publishers, with Elsevier being the most frequently utilized. This study contributes to the literature by offering insights into recent trends and areas of focus in water sustainability accounting research, informing future research directions and policy-making efforts to address social, environmental, and economic challenges effectively.